The mitochondrial superoxide dismutase A16V polymorphism in the cardiomyopathy associated with hereditary haemochromatosis. Issue 12 (9th December 2004) - Valenti, L; Conte, D; Piperno, A; Dongiovanni, P; Fracanzani, A L; Fraquelli, M; Vergani, A; Gianni, C; Carmagnola, L; Fargion, S
Abstract : The A16V mitochondrial targeting sequence polymorphism influences the antioxidant activity of MnSOD, an enzyme involved in neutralising iron induced oxidative stress. Patients with hereditary haemochromatosis develop parenchymal iron overload, which may lead to cirrhosis, diabetes, hypogonadism, and heart disease. The objective of this study was to determine in patients with haemochromatosis whether the presence of the Val MnSOD allele, associated with reduced enzymatic activity, affects tissue damage, and in particular heart disease, as MnSOD knockout mice develop lethal cardiomyopathy. We studied 217 consecutive unrelated probands with haemochromatosis, and 212 healthy controls. MnSOD polymorphism was evaluated by restriction analysis. The frequency distribution of the polymorphism did not differ between patients and controls. Patients carrying the Val allele had higher prevalence of cardiomyopathy (A/A 4%, A/V 11%, V/V 30%, p = 0.0006) but not of cirrhosis, diabetes, or hypogonadism, independently of age, sex, alcohol misuse, diabetes, and iron overload (odds ratio 10.1 for V/V, p = 0.006). The frequency of the Val allele was higher in patients with cardiomyopathy (0.67 v 0.45, p = 0.003). The association was significant in both C282Y+/+ (p = 0.02), and in non-C282Y+/+ patients (p = 0.003), and for both dilated (p = 0.01) and non-dilated stage (p = 0.04) cardiomyopathy, but not for ischaemic heart disease. In patients with hereditary haemochromatosis, the MnSOD genotype affects the risk of cardiomyopathy related to iron overload and possibly to other known and unknown risk factors and could represent an iron toxicity modifier gene.